Os passos da fé : um olhar etnográfico sobre a peregrinação a Divina Pastora - Oliveira, Izabel Cristina Ferreira (2012)
This dissertation is focused on the study on the pilgrimage to the Divina Pastora, a municipality of the State of Sergipe. The issue concerns the efforts made by the pilgrims, to make this journey, experiencing the hardships of the journey of nine miles. The main objective was to conduct an anthropological study of religious ritual, from the perspective of relations between the pilgrim and divinity, which is consolidated from the payment of pledges in thanks to the graces obtained, which in most cases are related to miracle cures . We began the work by making a historical approach, analyzing the context in which the pilgrimage was established in the State of Sergipe and how the tradition is recreated year after year. The emphasis on pilgrimages to literature and historical documents, including the books falls church city Divina Pastora and the Metropolitan Curia of Aracaju. Through ethnographic data, we identify the universe of pilgrimage on the pilgrim's point of view, analyzing the socio-cultural profile and their reasons for pilgrimage. The central idea was to understand the reasons why the pilgrims to the Shrine of the Divine Shepherdess.